Methods of estimation of coefficient of repeatability in rubber tree breeding - Vasconcellos, Maria Elizabeth da Costa; Gonçalves, Paulo de Souza; Paiva, João Rodrigues de; Valois, Afonso Celso Candeira (Pesquisa Agropecuaria Brasileira, 2014)
This study was undertaken to test various repeatability coefficient estimation procedures, as well as to determine the adequate number of minitest of production in the selection of seedlings in rubber tree nursery. Three minitests were run on open-pollinated progeny seedlings of the RRIM 600 clones and the coefficient of repeatability estimated by using both the analysis of variance and principal components techniques, described by Mansour and co-workers. The equation that relates all three minitests of production explained about 87% of the existing variations among test. Since no marked differences among tests procedures were found in the estimation of the coefficient of repeatability, the ANOVA technique is recommended, due to its simplicity.